PENINGKATAN HASIL BELAJAR IPA TENTANG SISTEM TATA SURYA MELALUI MEDIA AUDIO VISUAL DI SEKOLAH DASAR - Riris Trianingsih (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
Solar system material in the science learning process, some students have difficulty understanding the teaching material. So that their value is still below the KKM. For this reason, researchers conducted Classroom Action Research (CAR) using audio-visual media. The purpose of this study was to improve student learning outcomes by using audio-visual media. The object of this research is the sixth grade students of SDN 8 Suwawal, Jepara. Which has a total of 22 students consisting of 13 male students and 9 female students. This research was conducted in stages with 3 cycles. The results of this study an increase from each cycle, this can be seen from the average value of cycle 1 is 55.90 with a completeness rate of 31.8%. While the average value of 11 cycles is 70.9 with a completeness value of 59.10%. Then the average value of the cycle is 111.84.1 with a completeness value of 100%.